2022
DOI: 10.3390/min12101291
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Applicability of Agitated Cyanide Leaching and Thiosulphate Leaching for Gold Extraction in Artisanal and Small-Scale Gold Mining

Abstract: Mercury amalgamation is the method of choice to recover gold in artisanal and small-scale gold mining (ASGM). However, despite the low cost and simplicity of this method, the use of mercury presents serious health and environmental risks, as well as low efficiency in gold extraction. This study investigates the application of cyanide and thiosulphate leaching as alternatives to mercury amalgamation. This investigation was undertaken by conducting leach experiments using cyanide at 1 g/L, 3 g/L, and 5 g/L, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
0
1
0
1
Order By: Relevance
“…Figura 8. Mapa bibliográfico de la lixiviación del oro con cianuro El diagrama anterior muestra que las investigaciones relacionadas con la lixiviación del oro con cianuro van encaminadas a reducir el consumo de cianuro en el proceso de disolución, ya sea adicionando nitrato de plomo como catalizador (Soltani et al, 2020), variando la fuente del reactivo usando cianuro biogénico (Faraji et al, 2021), o al utilizar sistemas de disolución compuestos por cianuro y otro solvente para el oro, como los sistemas cianuro-tiosulfato o el cianuro-glicina (Manzila et al, 2022). Al ser un método ya establecido de disolución, las investigaciones suelen estar relacionadas más a cómo lidiar con los efectos nocivos que tiene este reactivo, es común encontrar artículos hablando de remediación de suelos, descomposición de cianuro o tratamiento de aguas con contenidos de cianuro (Xiong et al, 2021).…”
Section: Pág 2423unclassified
“…Figura 8. Mapa bibliográfico de la lixiviación del oro con cianuro El diagrama anterior muestra que las investigaciones relacionadas con la lixiviación del oro con cianuro van encaminadas a reducir el consumo de cianuro en el proceso de disolución, ya sea adicionando nitrato de plomo como catalizador (Soltani et al, 2020), variando la fuente del reactivo usando cianuro biogénico (Faraji et al, 2021), o al utilizar sistemas de disolución compuestos por cianuro y otro solvente para el oro, como los sistemas cianuro-tiosulfato o el cianuro-glicina (Manzila et al, 2022). Al ser un método ya establecido de disolución, las investigaciones suelen estar relacionadas más a cómo lidiar con los efectos nocivos que tiene este reactivo, es común encontrar artículos hablando de remediación de suelos, descomposición de cianuro o tratamiento de aguas con contenidos de cianuro (Xiong et al, 2021).…”
Section: Pág 2423unclassified
“…Studies have shown that this activity is economically important for rural communities and reducing poverty [6]. The informal mining practice of amalgamation, as determined by Ecuadorian legislation [7,8], is the predominant method of extracting Au [9]. Amalgamation is one of the oldest processes used in gold recovery [10].…”
Section: Introductionmentioning
confidence: 99%